2021
DOI: 10.1136/bmjspcare-2021-003087
|View full text |Cite
|
Sign up to set email alerts
|

Designing the physical environment for inpatient palliative care: a narrative review

Abstract: BackgroundIt is essential that the physical environments in which inpatient palliative care is provided support the needs of patients and the facilitate the multidimensional delivery of palliative care. This review aims to identify the features and characteristics of inpatient palliative care environments that enhance or detract from the patient experience; and identify opportunities for progress within this field.MethodThree databases were searched: MEDLINE (1946–2020), PsycINFO (1806–2020) and CINAHL (1937–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In a recent review, Wong et al (2021) highlight two limitations within the extant literature for the design of palliative care environments: the assumption that a private room is the best architectural solution to upholding patient dignity and the risk of reducing homeliness to simple matters of interior design (also see McLaughlan & Kirby, 2021). Privacy, as the staff perceptions reported above make evident, is a design concern that reaches far beyond the bedroom and bathroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Wong et al (2021) highlight two limitations within the extant literature for the design of palliative care environments: the assumption that a private room is the best architectural solution to upholding patient dignity and the risk of reducing homeliness to simple matters of interior design (also see McLaughlan & Kirby, 2021). Privacy, as the staff perceptions reported above make evident, is a design concern that reaches far beyond the bedroom and bathroom.…”
Section: Discussionmentioning
confidence: 99%
“…A reliance on design evidence from other healthcare settings may be exacerbating this problem. A recent review identified only a dozen studies that expressly examined the design of palliative care settings (Wong et al, 2021). This limitation of available research means design evidence from other healthcare settings is often adopted for use (see, e.g., Irish Hospice Foundation, 2009; Zadeh et al, 2018).…”
mentioning
confidence: 99%
“…2015). Precisely what constitutes the attainment of homeliness, however, or even the particular design strategies for obtaining it, is nowhere explicitly defined (Wong et al . 2021).…”
Section: Imparting Care Through the Built Environment: Design Intent ...mentioning
confidence: 99%
“…While participants acknowledged the importance of soft furnishings, and of mitigating the appearance of medical equipment, they also spoke of comfort in terms of sensory experience, accessibility, recognising the need for individual choice and alleviating situational unease. This suggests that what is missing from much of the evidence-based design literature for palliative care is an expanded definition of comfort; one that is more explicit about the fact that there is more to homeliness than soft furnishings (also refer Wong et al . 2021).…”
Section: Imparting Care Through the Built Environment: Design Intent ...mentioning
confidence: 99%
See 1 more Smart Citation